2015
DOI: 10.1186/s12877-015-0075-3
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prevalence of dementia in linked administrative health data in Saskatchewan, Canada: a retrospective cohort study

Abstract: BackgroundDetermining the epidemiology of dementia among the population as a whole in specific jurisdictions – including the long-term care population–is essential to providing appropriate care. The objectives of this study were to use linked administrative databases in the province of Saskatchewan to determine the 12-month incidence and prevalence of dementia for the 2012/13 period (1) among individuals aged 45 and older in the province of Saskatchewan, (2) according to age group and sex, and (3) according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 33 publications
3
23
1
Order By: Relevance
“…Rates of clinically diagnosed dementia are, as expected, lower than rates recorded in field-based studies based on case finding [1618], because some people with early dementia found in the case finding studies may not have been clinically diagnosed and thus would not have been recorded as having dementia in primary care data. Those diagnosed with dementia in primary care would not necessarily be admitted to hospital, and not all those admitted would have had dementia coded in their hospital records.…”
Section: Discussionsupporting
confidence: 59%
“…Rates of clinically diagnosed dementia are, as expected, lower than rates recorded in field-based studies based on case finding [1618], because some people with early dementia found in the case finding studies may not have been clinically diagnosed and thus would not have been recorded as having dementia in primary care data. Those diagnosed with dementia in primary care would not necessarily be admitted to hospital, and not all those admitted would have had dementia coded in their hospital records.…”
Section: Discussionsupporting
confidence: 59%
“…The Sydney Older Persons study provides one relatively recent Australian comparison and similarly shows slightly higher incidence rates to the current study, although it is based on a small sample 27 . The rates observed in the current study are consistent with other studies internationally using administrative data 28 .…”
Section: Discussionsupporting
confidence: 92%
“…22 This algo rithm identified a new diagnosis of dementia using any of 3 cri teria: from the CIHI Discharge Abstract Database, a relevant International Statistical Classification of Diseases and Related Health Problems, 10th revision code recorded on hospital discharge; from the Ontario Health Insurance Plan, a relevant diagnostic billing code recorded on 3 physician billings separated by 30 days, within a 2year period; or from the Ontario Drug Benefit program, the dispensing of any cholinesterase inhibitor. As a result of known underdiagnosis and documentation of dementia by phys icians 23,24 and moderate sensitivity from the validated algorithm used, 22 we supplemented this definition by including individuals identified as having dementia through assessments for home care (Resident Assessment InstrumentHome Care) and longterm care (Continuing Care Reporting System). 25 We considered the date on which dementia was first documented to be the index date.…”
Section: Dementia Cohort Selectionmentioning
confidence: 99%